WOMEN, BUSINESS, MICRO SMALL MEDIUM ENTREPRISES AND PUBLIC SERVICES: AN EMPIRICAL ANALYSIS - Ipung Sri Purwanti Hery (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Business to business direct marketing in a Micro, Small and Medium Enterprises (MSMEs) has many opportunities and considerations in the next 25 years. In the past, success was determined by a simple focus and attention to small things. In the middle of the next century, direct marketers will be pushed into economic, technological, social and cultural changes. Like the waves hitting the shore, many changes occur slowly and not all of them occur. However, small, logical, and structural changes will occur. Finally, over a long period of time, permanent changes in the mass market and business-to-business direct marketing industry will occur. The main elements of cause and effect are: economic, technological, social and cultural forces. Each element has dominance over the change process. Each element will enter into unstoppable momentum and collide with the current static state. Nothing will be like it is now-not in a second, an hour, a year, or a century. Business-to-business direct marketers who observe, think and project ahead based on economic logic, technological advantages, and social interests are sure to succeed. Keywords: Women, Business, MSMEs, Public Service